Solid-liquid extraction of Rare Earth Elements from Indonesian Wacopek bauxite tailings by the sulfuric acid leaching and precipitation methods - Kusrini, Eny, Kusrini, Eny; Muharam, Yusman; Aulia, Merisa; Usman, Anwar; Prasetyo, Agus Budi; Sofyan, Nofrijon; Suyanti; Dhaneswara, Donanta; Suwartha, Nyoman; Ivo, Ponky; Aprilio, Franklin; Wilson, Lee D.; et al. (Penerbit Universiti Kebangsaan Malaysia, 2025)
The high demand of rare earth elements (REEs) and geopolitical issues affecting their supply. Thus, a number of research have been conducted to find some secondary resources for producing of REEs. The work is aimed to extract of total REEs (TREEs) from Indonesian Wacopek bauxite tailing by solid-liquid extraction using sulfuric acid with concentrations being 1.5 to 5 M and the precipitation methods. Leaching and enrichment of total REEs from the bauxite tailings employed sulfuric acid as the solvent, where precipitation occurred in two stages using sodium sulfate and sodium phosphate as well as leaching kinetic have been investigated. The final extracted REEs are in the forms of their hydroxides. The experimental was conducted in the batch system by varying leaching time (5 to 60 min) and temperature (25 to 60 °C). Metal separation from the leachate was carried out by a solid-liquid extraction in H2 SO4 at a liquid/solid (L/S) ratio of 20 mL/g, according to the optimal operating temperature at 60 °C, leaching time of 30 min, concentration of H2 SO4 of 3 M, leachate volume of 500 mL, and L/S ratio of 20 mL/g. In the total REEs precipitation process with subsequent NH4 OH-sodium sulfate and NH4 OH-sodium phosphate precipitant system yielded 0.23 g and 9.8 g of REEs-sulfate and REEs-phosphate, respectively. The final REE-hydroxides gave the maximum total REEs yield as high as 90.75%. Leaching kinetics study was described by the shrinking core model for unchanged spherical particle sizes, and acid leaching occurred in two steps that governed by chemical reaction and diffusion process. The activation energy in the first chemical process was characterized to be 10.1 kJ/mol and the second diffusion process was 15.5 kJ/mol. In this work, the solid-liquid extraction process used sulfuric acid to bind to the TREEs contained in the Wacopek dried bauxite tailing potential for further separation of TREEs.